The barriers and facilitators of engaging in remote work in the open labour market for paid employment, as experienced by persons with spinal cord injuries (SCI) within the Gauteng Metropole. - Swart, Alicia (Stellenbosch : Stellenbosch University, 2022)
Thesis (MOccTher)--Stellenbosch University, 2022.